Arndt's story : the life of an Australian economist - Coleman, Peter, 1928- (ANU E Press : Asia Pacific Press, 2007)
"H.W. Arndt has been Australia's leading scholar of Asian economic development for over thirty years"--Former World Bank President James D Wolfensohn. The year of Heinz Wolfgang Arndt's birth, 1915, was not a good time for a German boy to be born. His country was soon to be defeated in a great war, his school years were shadowed by the rise of Hitler. Yet when Heinz's long-buried Jewish background led his academic father to lose his chair in chemistry and flee to Oxford, Heinz followed. As Heinz put it, the calamity of Hitler's rise to power led him to 'the incredible good fortune of an Oxford education and a life spent in England and Australia.' This was a man of inexhaustible energy and optimism, who returned from months behind barbed wire interned in Canada to write a historical classic-The Economic Lessons of the Nineteen-Thirties. He seized the opportunity of an unexpected job offer to set off with his young family for Sydney where he quickly established himself as a leading authority on the Australian banking system, embarked on his fifty year career as a gifted university teacher and enjoyed the first of many vigorous forays as a public intellectual. But it was at ANU that Heinz took the bold step which led him to become the Grand Old Man of Asian Economics. In 1966, just after the Sukarno coup and the year of living dangerously, he determined the time had come to study the Indonesian economy. It took all his charm, persistence and formidable intellect to persuade the Indonesians to open their doors to him. The result was a world-leading centre of Indonesian economics which greatly contributed to the development of modern Indonesia